CuCN-Mediated cascade cyclization of 4-(2-bromophenyl)-2-butenoates: a high-yield synthesis of substituted naphthalene amino esters - Reddy, R. Santhosh; Prasad, Pragati K.; Ahuja, Brij Bhushan; Sudalai, Arumugam (Journal of Organic Chemistry, 2013)
A new method of CuCN-mediated one-pot cyclization of 4-(2-bromophenyl)-2-butenoates leading to efficient synthesis of substituted naphthalene amino esters including phenanthrene aromatic structural units is described. Deuterium labeling studies establish that this one-pot cascade cyclization proceeds through isomerization of olefin, intramolecular C-C bond cyclization, and aromatization as the key intermediates, all occurring in a single step.

Copper(I) bromide-catalyzed carbonylative coupling of aryl halides with phenols, alcohols and amines using sodium cyanide as C-1 source: a synthesis of carboxylic acid derivatives - Prasad, Pragati K.; Sudalai, Arumugam (Advanced Synthesis & Catalysis, 2014)
A new ``carbon monoxide-free'' synthesis of carboxylate derivatives via carbonylative coupling of aryl bromides with phenols, alcohols, amines and acids in the presence of copper(I) bromide as catalyst and sodium cyanide in a stoichiometric amount has been developed. Its intramolecular version provides for the preparation of lactones (e.g., isochroman-1-ones and isobenzfuranones), imides, anhydrides and lactams in excellent yields (73-96%).
Keywords: anhydrides; C-1 building blocks; isochroman-1-ones; lactams; lactones

Concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol using Co(III)(salen)-catalyzed hydrolytic kinetic resolution of a two-stereocentered anti-azido epoxide - Reddi, Rambabu N.; Prasad, Pragati K.; Kalshetti, Rupali G.; Sudalai, Arumugam (Tetrahedron-Asymmetry, 2017)
A concise enantioselective synthesis of 1,4-dideoxy-1,4-imino-D-arabinitol, (+)-DAB-1, has been described in good overall yield (18.1%) and with high enantiomeric purity (up to 98% ee) starting from a simple raw material, cis-2-butene-1,4-diol. The Co-catalyzed hydrolytic kinetic resolution of a two-stereocentered racemic azido epoxide followed by asymmetric dihydroxylation of the alkene and 'one pot' reductive cyclisation of the azido diol are key reactions in the synthetic sequence. (C) 2016 Elsevier Ltd. All rights reserved.